De Paris à Padoue, le grand tour d’un universitaire proscrit par Louis XIV : Charles Patin, médecin, numismate (1633-1693) - Patrick Ferté (Les Cahiers de Framespa)
Famous Guy Patin’s son, Charles Patin is a physician and precursor numismatist, whose academic career at Paris was early crushed by Louis XIV, because of free-thinking and forbidden books traffic. Escaped before imprisonment (1667), he saw his destiny started up again at the end of a Grand Tour throw the Republic of Letters, about which he kept a precious diary. This peregrinatio academica led the outlaw to Padoua University, where Venetian Republic recruited him as a defiance hurled at French militar and cultural hegemony. Patin found a family there and became the kingpin of padouan and venetian intellectual sociability, which he revived, both with his medical, numismatical and historiographical productions than with his academic initiatives, notably feminist.